Fred rant - Juhasz, Alexandra (Transformative Works and Cultures, 2012)
A compilation of videos and commentary about Fred, a popular teen YouTuber with the persona of a 6-year-old child.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzk4My90d2MuMjAxMi4wMjk1